Pelatihan Branding Digital dan Repackaging Produk UMKM di Desa Pilanjau - Nurhidayati, Safitri; Adi Purwanto, Sayugo; Kania Indraswari, Dara; Sulpadli, Sulpadli; Nurhaliza, Nurhaliza (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
Given the increasingly competitive nature of the workplace and business world, micro, small, and medium-sized enterprises (MSMEs) are being challenged to adapt to technological advancements, evolving mindsets, and consumer preferences in today's modern era. Current evidence suggests that many MSMEs have yet to address digital branding and product repackaging. Digital branding is the process of creating and managing a brand's identity and reputation online. This process involves using various digital channels and tools to promote a brand, engage customers, and build a strong online presence. Repackaging refers to the act of putting something into new packaging or a new container. It is the process of changing a product's original packaging, often for various strategic reasons. The Pilanjau Village MSME Product Digital Branding and Repackaging Training was successfully implemented and received a positive response from the participants, the majority of whom were local MSMEs. Through this activity, participants gained fundamental knowledge and practical skills regarding the importance of digitally building a brand identity (branding) and how to repackage products to create a more attractive and professional appearance. This training successfully opened participants' minds to the fact that branding and packaging are not merely about appearance, but are strategic elements in increasing product competitiveness in the modern marketplace, both offline and online. Going forward, further mentoring is needed to ensure participants can consistently implement the knowledge gained in their businesses.